A Comparison of Social Health Components Among the Farmers in the Villages of Saffron and Other Plants in South Khorasan Province - Ismaeel Jahanbakhsh (Gonabad University of Medical Sciences, 2021)
Background: Social health is defined as the individual’s ability to effectively and efficiently play social roles without hurting other people. It is the examination of an individual’s activities and status in society. Saffron cultivation, given its special properties, such as teamwork, cooperation, and social correlation, plays a major role in social health. Thus, the current study was done to compare the social health components among the farmers in saffron villages and the others in South Khorasan Province. Methods: The current study was applied and comparative. The statistical population included the farmers in saffron villages and the others in South Khorasan Province in 2018. The sample consisted of 550 farmers (275 producing saffron and 275 producing other plants) based on the Cochran formula who were selected through multistage sampling. The tool used to collect the data was Keyes’s standard Social Well-being Questionnaire (2004), consisting of 28 questions. After collecting the questionnaires, the data were analyzed using SPSS v. 23 and an independent t-test at a significance level of P<0.05. Results: There was a significant difference between the villagers planting saffron and other plants regarding their social health levels (P<0.000). The obtained t-value for social health, as a dependent variable, was 15.47. The obtained t-value for all the aspects of social health was higher than the acceptable t-value (P<0.05). Conclusion: The results showed that saffron villages had higher social solidarity, compared to other plants. Because cooperation and collaboration are necessary for different stages of saffron production, social cohesion is naturally reinforced.